2023
DOI: 10.24940/theijhss/2023/v11/i1/hs2301-012
|View full text |Cite
|
Sign up to set email alerts
|

Early Children Education through Arts: Pre-school Teachers Views on Types and Frequency of Young Children Engagement in Music Education Activities in Pre-school Settings in Greece

Abstract: The aim of the present study was to examine the frequency of implementing musical activities in the weekly pre-school settings program and the type of musical activities that pre-school teachers choose to implement. Factors that may influence the frequency of implementing musical activities were also investigated. In addition, some indications and changes recommended by pre-school teachers themselves, which would support and facilitate a more frequent implementation of musical activities in the pre-school sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Nevertheless, we rarely identified such features in the reports. In addition, the QR reports tended to reflect a teacher-oriented perspective of kindergarten music education, given that teachers play a crucial role in facilitating quality music education [7,8]. However, the reports offered limited recommendations to improve teachers' music pedagogies and children's musical learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we rarely identified such features in the reports. In addition, the QR reports tended to reflect a teacher-oriented perspective of kindergarten music education, given that teachers play a crucial role in facilitating quality music education [7,8]. However, the reports offered limited recommendations to improve teachers' music pedagogies and children's musical learning.…”
Section: Discussionmentioning
confidence: 99%
“…In prior interview studies, ECE teachers highlighted the importance of their own role as facilitators of quality music education, predominately focusing on how teachers should prepare, design, and implement musical activities in ECE classrooms [7,8]. For example, in an interview study conducted in the United States by Flores [9], kindergarten teachers suggested quality teaching examples to integrate music with other learning areas.…”
Section: Perspectives and Practices On Ece Music Education Around The...mentioning
confidence: 99%